USE OF INFORMATION COMMUNICATION TECHNOLOGIES AT DRAWING AND DIZING LESSONS (Web of Technology: Multidimensional Research Journal, 2024)
The article discusses the ways of maintenance and gives theoretical materials on the preparation of students of secondary educational schools in the classroom of fine art. Theoretical materials have been developed on various topics that develop students' images that serve to shape the skills of their use of modern computer technologies.